RANTAI PASOK BAWANG MERAH VARIETAS SUMENEP DAN MITIGASI RISIKONYA - E SUPRIYADI, TUTI KARYANI, FUJI NUR AZIZAH, ENDAH DJUWENDAH, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
Sidamulya Village is a center for producing shallots in Jalaksana District, Kuningan Regency. In the village there is a Mekarjaya 1 farmer group that has marketed its products, namely sumenep fried onions to the fried onion industry. The demand for sumenep shallots is continuous every day, so the supply of shallots must be continuous as well. There were several actors involved in the shallot supply chain that have a business process and bear certain risks. Therefore this study was conducted to analyze the risks that arise from each supply chain actor, as well as mitigation to minimize losses caused by using the House of Risk (HOR) method. The results showed that there were 17 priority risks consisting of 4 risks to farmers, 4 risks to dealers, 4 risks to PO Mekar Wangi and 5 risks to POSedap Wangi. The risk mitigation that can be done by the Mekarjaya Farmers Group 1 is the use of pesticides, the risk mitigation that can be carried out by the dealer is to inform farmers about setting cropping patterns, risk mitigation that can be done by PO Mekar Wangi is to increase product variation, and mitigate risks that can done by PO Sedap Wangi is expanding marketing.Keywords : Â Shalot Supply Chain, House of Risk (HOR), Mitigation Action